A new timeline for deindustrialization: The movement of auto corporations in the US and Detroit - Jackson Battista (Essays in Economic & Business History (EEBH), 2022)
This article takes the first step in attempting to create a more accurate timeline of deindustrialization, whichis generally understood as a process that begins and proceeds through the 1970s. Iarguethat thisnarrative of deindustrialization, which is very much tied to 1970s events, should be called into question, asthe empirical evidence on corporate relocation tells a different story. Thearticletracks the regional movement of auto corporations out of Detroit and establishes a new timeline for corporate migration and deindustrialization, well before this generally accepted 1970s starting point. To do this it makes use of multiple collections housed in the Reuther Archives at Wayne State University and Moody's Industrial Manual Reports. Inquestioningthe established timelineof deindustrialization, the article highlightsother aspects of the process itself.
Keywords: N00; N62; B50; P00; 330; deindustrialization; economic history; Detroit; Michigan; political economy